(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article analyzes the production, circulation, and significance of cerebrospinal fluid (CSF) in the normal functioning of the central nervous system. The study results demonstrate that CSF plays a crucial role in protecting the brain and spinal cord, removing metabolic waste, and delivering necessary substances. It is also emphasized that disruptions in CSF circulation can lead to pathologies such as hydrocephalus.